ANALISIS KINERJA KEUANGAN DAN FINANCIAL DISTRESS PERBANKAN SYARIAH DI INDONESIA - Sari, Dian Wulan; Husaini, Husaini; Usman, Darman (UNIB Press, 2017)
The growth of Islamic banking is currently progressing. This is evidenced was many founding Islamic banks after Muamalat Bank. But this doesn’t mean that the inevitable progress of financial distress. Financial distress can be avoided if the financial performance in a good condition. This research to analyze the influence of CAMEL financial ratios the financial distress of Islamic banking in Indonesia, so that bank management can anticipate the financial distress.This research used secondary data from Quarterly Financial Statements and Report of Good Corporate Governance (GCG) from 2011-2014. The variables used were 9 financial ratios, they are: CAR, KAP, GCG, NOM, ROA, ROE, REO, STM, and FDR. The Samples were obtained by using random sampling method, as many as 9 Islamic Banks (BUS) of a total population of 11 BUS. The Analyzer used is the Logistic Regression.The results of logistic regression test showed that the ratio of CAR, GCG, NOM, ROA, STM, and FDR had no significant effect negatively on the financial distress of Islamic banking in Indonesia, the ratio of REO positively no significant effect on the financial distress of Islamic banking in Indonesia. While KAP and ROE ratios negatively significant effect on the financial distress of Islamic banking.